2013
DOI: 10.1063/1.4817883
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states in hybrid boron nitride and graphene structures

Abstract: The energy bands and electronic states of hybrid boron nitride (BN) and graphene structures are studied by first principle calculations. The electronic states change from semi-metallic to insulating depending on the number of B and N atoms as well as domain symmetry. When there are unequal numbers of B and N atoms, mid-gap states usually appear around the Fermi level and the corresponding hybrid structure possesses magnetic and semi-metallic properties. However, when the numbers of B and N atoms are equal, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…It must be noted here that there are two types of band gap convergence with respect to the distance between the embedded B 3 N 3 units: one for lattices in which the cell size is a multiple of 3, (B 3 N 3 ) m @G n × n ( m = 1, 4 and n = 3, 6, 9) and one for those with n = 4, 5, 7, 8. This effect has been documented and explained in earlier studies on carbon nanotubes and on graphene antidot lattices with zigzag vacancy edges by Ouyang et al and by Zhao et al in h BNG doped with small hexagonal stoichiometric hBN patches, including B 3 N 3 as those we considered here. At the bottom of Figure , we compare the band gap evolution on B 3 N 3 @G 7×7 and B 3 N 3 @G 9×9 as a function of the method used with the respective evolution on two finite graphene flakes doped with six borazine rings bearing different sizes and edge structures.…”
Section: Resultssupporting
confidence: 81%
“…It must be noted here that there are two types of band gap convergence with respect to the distance between the embedded B 3 N 3 units: one for lattices in which the cell size is a multiple of 3, (B 3 N 3 ) m @G n × n ( m = 1, 4 and n = 3, 6, 9) and one for those with n = 4, 5, 7, 8. This effect has been documented and explained in earlier studies on carbon nanotubes and on graphene antidot lattices with zigzag vacancy edges by Ouyang et al and by Zhao et al in h BNG doped with small hexagonal stoichiometric hBN patches, including B 3 N 3 as those we considered here. At the bottom of Figure , we compare the band gap evolution on B 3 N 3 @G 7×7 and B 3 N 3 @G 9×9 as a function of the method used with the respective evolution on two finite graphene flakes doped with six borazine rings bearing different sizes and edge structures.…”
Section: Resultssupporting
confidence: 81%
“…Metal-modified graphene hybrid materials have been widely used in oxygen reduction reactions, , batteries, supercapacitors, catalysis, and photocatalysis . Moreover, it has been reported that the electronic structure of graphene can be significantly modified by the introduction of certain heteroatoms, such as N and B . Therefore, their catalytic properties were altered as a consequence, which was also previously reported in carbon nanotube system for oxidative dehydrogenation of alkanes and carbon nitride system for cyclohexane oxidation. Particularly, graphene and heteroatom-modified graphene were reported to be able to catalyze various catalytic reactions, such as hydrogenation, polymerization, alcohol oxidation, oxidative coupling, and even C–H bond activation. However, until now, there has been no report on the catalytic epoxidation of a double bond over a graphene catalyst.…”
mentioning
confidence: 67%
“…Apart from the size and shape of the graphene domain, the effect of the graphene edge structure on the band gap has also been explored. By using a tight‐binding model, Zhao et al found that the dependence of the electronic properties on the edge structures of graphene domains was removed when they were incorporated into BN nanosheets, i.e., the gap for graphene domains with zigzag edges was identical to that for armchair ones. In contrast, using first‐principles calculations, Ding et al indicated that if the graphene was embedded in BN nanosheets in the form of nanoribbons, a semiconductor could be achieved for a system with armchair graphene nanoribbons as well as narrow zigzag graphene nanoribbons, and a half‐metal could be acquired for a system with wider zigzag graphene nanoribbons .…”
Section: Physical Propertiesmentioning
confidence: 99%